Demystifying Interoperability. Insights from our work in Ethiopia's ag riculture sector - Hatcher-Mbu, Beverley; Ferreyra, Fernando; Postelnicu, Mihai; Cihai, Viorel; Getachew, Yosef; FIkre, Yohannes; Kassa, Selam; Orrell, Tom; Tewari, Khyatee (Development Gateway, 2024)
Government offices are filled with siloed, sector-specific digital sys tems that strain their capacity to make decisions, use data effectivel y, and achieve ambitious sustainable development goals. Public investm ents in digital development, transformation, and infrastructure can on ly meet citizen needs if data and systems are consolidated and interop erable. While interoperability is a sensible approach to building digi tal public infrastructure, transforming existing systems is easier sai d than done. Limited resources and expertise, lack of training, inadeq uate hardware and software infrastructure, and concerns over data priv acy are some of the key factors that limit the impact of systems or le ad to their discontinuation. The data that feeds these systems also ne eds to be standardized using global best practices and common language s and frameworks that can be understood across multiple platforms and adapted to the local context. In increasingly digital economies, syste ms and their data need to be relevant and responsive to citizens’ spec ific conditions and needs With emerging challenges like climate change that require more complex data, and new technologies like artificial intelligence (AI) that require large volumes of data, systems need to be agile and scalable to advance solutions and fully harness innovatio n. This paper discusses, in practical terms, what goes into implementi ng interoperable solutions in partnership with public administrations. Based on 20+ years of DG’s experience, the paper demystifies key comp onents needed to build robust, resilient, and interoperable data syste ms, focusing on the “how” of data standardization, data governance, an d implementing technical infrastructure.